2001
DOI: 10.1021/bi010801u
|View full text |Cite
|
Sign up to set email alerts
|

The Tetrahymena Ribozyme Cleaves a 5‘-Methylene Phosphonate Monoester ∼102-fold Faster Than a Normal Phosphate Diester:  Implications for Enzyme Catalysis of Phosphoryl Transfer Reactions

Abstract: Single-atom substrate modifications have revealed an intricate network of transition state interactions in the Tetrahymena ribozyme reaction. So far, these studies have targeted virtually every oxygen atom near the reaction center, except one, the 5'-bridging oxygen atom of the scissile phosphate. To address whether interactions with this atom play any role in catalysis, we used a new type of DNA substrate in which the 5'-oxygen is replaced with a methylene (-CH2-) unit. Under (kcat/Km)S conditions, the methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…Oligomers 16-18 and 4 0 0 -C-methyl phosphodiester dT 15 Oligomer 19 The solid-phase syntheses of phosphonate oligomers 16-18 were performed from the 5 0 -end on a GenSyn (IOCB Prague) synthesizer using CPG support modified with 2 0 -deoxy-3 0 -O-DMTr-thymidine-5 0 -hemisuccinate (0.5 mol scale). The preparation of oligonucleotide 16 with all-phosphonate backbone was carried out with the monomer 15a (and its homooligomeric counterpart with ''phosphonate-down'' -D-erythro configuration likewise with 15b; not shown) by the phosphotriester method 13,27,28 whereas the oligomers with mixed phosphonate-phosphodiester linkages 17 and 18 ( Figure 2) were prepared by alternating incorporation of a ''reversed'' amidite, the 3 0 -O-dimethoxytritylthymidine 5 0 -O-(cyanoethyl-diisopropylphosphoramidite), and the phosphonate monomer 15a or 15b using the phosphoramidite and phosphotriester protocols in the respective elongation steps.…”
Section: Synthesis Of Phosphonate Dt 15mentioning
confidence: 99%
See 2 more Smart Citations
“…Oligomers 16-18 and 4 0 0 -C-methyl phosphodiester dT 15 Oligomer 19 The solid-phase syntheses of phosphonate oligomers 16-18 were performed from the 5 0 -end on a GenSyn (IOCB Prague) synthesizer using CPG support modified with 2 0 -deoxy-3 0 -O-DMTr-thymidine-5 0 -hemisuccinate (0.5 mol scale). The preparation of oligonucleotide 16 with all-phosphonate backbone was carried out with the monomer 15a (and its homooligomeric counterpart with ''phosphonate-down'' -D-erythro configuration likewise with 15b; not shown) by the phosphotriester method 13,27,28 whereas the oligomers with mixed phosphonate-phosphodiester linkages 17 and 18 ( Figure 2) were prepared by alternating incorporation of a ''reversed'' amidite, the 3 0 -O-dimethoxytritylthymidine 5 0 -O-(cyanoethyl-diisopropylphosphoramidite), and the phosphonate monomer 15a or 15b using the phosphoramidite and phosphotriester protocols in the respective elongation steps.…”
Section: Synthesis Of Phosphonate Dt 15mentioning
confidence: 99%
“…Mixing curves (not shown) of oligomers 17 and 19 with dA 15 (modified dT 15 :dA 15 ) exhibited flat minima, indicating the possible presence of both duplex and triplex structures. Because in this case the method did not allow for unambiguous determination of either simple stoichiometry of complex(es) or an equilibrium concentration of the duplexes and triplexes, the molecularity of the complexes could not be determined.…”
Section: Hybridization Of Novel Oligonucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…A deleterious impact on G binding to the Tetrahymena ribozyme is observed for a "dangling" 3 ′ U residue of S when the P1 helix is docked in active site (Liao et al 2001;Karbstein et al 2007), and this effect may be analogous to the observed inhibitory effect of the unpaired IGS extension or resulting unpaired 3 ′ -tail of CAUA 5 on the S-bound L-6A Azoarcus ribozyme. Fortuitous interactions may be common when residues are positioned within RNA "pockets," especially given the relatively simple hydrogen bonding and stacking recognition patterns in RNA (e.g., Peracchi et al 1996;Karbstein et al 2007).…”
mentioning
confidence: 98%
“…34 Comparison of the rate of methylene monoesters shows that changing this oxygen to carbon has only a small effect on reaction rate. A reexamination of previous physical organic analyses indicates that this group undergoes little charge buildup in the transition state; thus, enzyme interactions with this group are not expected to provide significant catalytic advantage.…”
Section: Transition States Of Phosphoryl Transfer Reactionsmentioning
confidence: 99%